Polyphosphate-reduced graphene oxide on Ni foam as a binder free electrode for fabrication of high performance supercapacitor. (10th February 2019) - Talebi, Majid; Asen, Parvin; Shahrokhian, Saeed; Ahadian, Mohammad Mahdi
Abstract: Polyphosphate reduced graphene oxide on Ni foam (PPO-RGO/NF) is synthesized by varying weight ratios of Na5 P3 O10 (PO): graphene oxide (GO) with a simple, scalable and low cost method through freeze-drying of the PO-GO/NF followed by thermal treatment of the prepared electrodes. The resulting samples are characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), Brunauer-Emmett-Teller (BET), and raman spectroscopy methods. The results show that the weight ratio of PO:GO, considerably affect the electrochemical properties of PPO-RGO/NF. Especially, the as-prepared PPO-RGO/NF with PO:GO weight ratio of 2:1 delivers a high specific capacitance of 118 F g −1 at a current density of 5 A g −1, and also the specific capacitance reaches 108 F g −1 with 92% capacitance retention after 3000 cycles. The good capacitive performance and cycling stability of the PPO-RGO/NF can be attributed to the collaborative effect of the electrical double layer capacitor of RGO and the pseudocapacitance characteristics from the faradaic reactions of the PPO groups. The as-prepared PPO-RGO/NF as the binder free electrode can be used to assemble a symmetric supercapacitor. Accordingly, PPO-RGO/NF based symmetrical supercapacitor with the mentioned weight ratio of PO:GO achieves some remarkable performances; good specific capacitance (30.9 F g −1 at 1 A g −1 ), energy density (2.47 Wh kg −1 at 523.48 W kg −1 ), and power density (2618 W kg −1 at 0.8 Wh kg −1 ). Graphical abstract: Image 1 Highlights: PPO-RGO is prepared on Nickel foam via a simple and low cost method. PPO-RGO is prepared at different weight ratios of PO:GO. The ratio of PO:GO shows significant influence on the electrochemical performance of the supercapacitors. PPO-RGO with PO:GO weight ratio of 2:1 shows a capacitance of 118 F g −1 at 5 A g −1 . Cycle life of PPO-RGO with PO:GO weight ratio of 2:1 is retained 92% after 3000 cycles.